Effect of surface treatments based on self‐assembling molecules and cerium coatings on the AA3003 alloy corrosion resistance. Issue 3 (9th August 2011) - Banczek, E. P.; Moraes, S. R.; Assis, S. L.; Costa, I.; Motheo, A. J.
Abstract This work presents the effects of a cerium conversion coating, self‐assembling molecules (SAM) treatment, and a combination of these two treatments on the corrosion resistance of the AA3003 alloy. The results were compared to that of a conversion coating treatment with hexavalent chromium (Cr VI). The corrosion resistance of the surface‐treated AA3003 alloy samples was investigated by electrochemical impedance spectroscopy and anodic polarization curves in 0.5 mol/L sodium sulfate solution with pH adjusted to 4.0. The results showed that the SAM treatment offered better corrosion protection for the AA3003 alloy than that provided by cerium conversion coating. The combination of cerium conversion and SAM treatments improved the corrosion resistance of the AA3003 alloy due to SAM adsorption on the alloy substrate exposed at the defects in the cerium conversion layer.